Performance Assessment for Mobile Base Station in UNITEN Vicinity - Nazri, Mohamad; Chin Hock, Goh; Roslan, Nurzanariah; Hamidah, Saidatul; Ferdous, Nayla (International Journal of Engineering and Technology, 2018)
This paper present the study at Received Signal Code Power (RCSP) and energy per chip divided by the total in-band interference (Ec/No) these parameters in order to provide good quality service to customers, mobile operator perform benchmarking project to monitor their quality of service which deliver to customer. The relation between these two parameters were discussed and proved from the drive test result at UNITEN vicinity. The method that used in this research was Network Planning Process and Data verification process. The fabrication and verification of data was done by using NEMO HANDY tools and HATA model. The aim is to carry out the test and research the Base Transceiver Station for mobile operation functionally and quality also collect the data and generate the report regarding the quality of voice call, call attempts, call fail, data network, attempt, data of RCSP and EC/No of the mobile operator. The result showed that the Telco B provide the best 3G service among the competitor and Telco D provide the 2G service compare the other operator. The relationship between RCSP and EC/No in path loss calculation is directly proportional to each other are proven. Besides that, it also proves that the terrain contour, site environment and antenna height will affect the throughput of the antenna transmitting power for mobile base station.Â